Challenges and perspectives on the use of mobile laboratories during outbreaks and their use for vaccine evaluation - Trina Racine; Gary P. Kobinger (Human Vaccines & Immunotherapeutics, 2019)
Mobile laboratories provide diagnostic capabilities for routine surveillance and patient identification during an outbreak. In either situation, they face many challenges including identification of the appropriate assay(s) to employ, logistical arrangements, and providing for the health and safety of the laboratory staff. Great strides have been made over the last decade in the development of mobile laboratories with assays that require minimal infrastructure and technical experience. This knowledge and expertise have been developed in partnership with many researchers and public health officials who live in regions prone to infectious disease outbreaks. Mobile laboratories should now also be used in the evaluation of novel vaccines and therapeutics in remote locations. Clinical mobile laboratories will include similar diagnostic capabilities as outbreak response mobile labs, but will also include additional point-of-care instruments operated under Good Clinical Practice guidelines. They will also operate rigorous data management plans so that the data collected will satisfy regulatory agencies during the licensure process. Failure to deploy an adequate clinical mobile laboratory when administering a novel biological product in a remote location is a significant limitation to any collected scientific data that could ultimately undermine clinical development and availability of life-saving interventions.